2020
DOI: 10.3847/1538-4357/ab5fd6
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Evolution of Neo-neutron Stars. I. Envelopes, Eddington Luminosity Phase, and Implications for GW170817

Abstract: A neo-neutron star is a hot neutron star that has just become transparent to neutrinos. In a core collapse supernova or accretion induced collapse of a white dwarf the neo-neutron star phase directly follows the proto-neutron star phase, about 30 to 60 seconds after the initial collapse. It will also be present in a binary neutron star merger in the case the "born-again" hot massive compact star does not immediately collapse into a black hole. Eddington or even super-Eddington luminosities are present for some… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…The initial temperature may change the thermal evolution. But, the dependence on the initial temperature seems to appear only up to ∼ 10 4 sec, the so-call neo-neutron stars era [67]. In this study, to avoid this dependence, we only consider the neutron star models at more than 1 year after they are born.…”
Section: Model Of Cooling Neutron Starsmentioning
confidence: 99%
“…The initial temperature may change the thermal evolution. But, the dependence on the initial temperature seems to appear only up to ∼ 10 4 sec, the so-call neo-neutron stars era [67]. In this study, to avoid this dependence, we only consider the neutron star models at more than 1 year after they are born.…”
Section: Model Of Cooling Neutron Starsmentioning
confidence: 99%
“…Processes such as DNB can significantly alter the envelope composition over time and can release additional heat, making it worthwhile to include the burning region of the envelope in future thermal evolution calculations. This would require setting the upper boundary of thermal transport equations to lower densities than ρ b = 10 8 or ρ b = 10 10 instead of using static temperature relations to connect the temperature at those densities to the temperature at the surface (see Beznogov et al 2020 for a more consistent treatment of the envelope applied to young neutron stars).…”
Section: General Effects Of Dnbmentioning
confidence: 99%
“…Comparing with the single NSs originating from the classic core-collapse SNe, the single NSs from the mergers of double WDs may correspond to a specific kind of NSs, showing some different properties, such as circumstellar environments and magnetic fields, etc. Beznogov et al (2020) recently suggested that the NSs originated from AIC may be observable during the neo-NS (i.e., hot NS) stage, in which the NS has just become transparent to neutrinos. Fig.…”
Section: Mass Distribution Of Nssmentioning
confidence: 99%